SUSTAINABILITY OF THE LIBYAN HOUSH IN THE OLD CITY OF TRIPOLI: استدامة الحوش الليبي في المدينة القديمة طرابلس - NADIR NASIR MOHAMMED SHEMBES (Journal of engineering sciences and information technology, 2019)
The ancient city of Tripoli was founded by Phoenicians around 3,000 years ago. As a result of various civilizations taking place, there are architectural and artistic works that constitute a real treasure in the city. The city, located in North Africa, has been serving as a transition between Europe and Africa. During Roman, Islamic States, Ottoman and Principalities period, especially commercial center and rich residences in this center were formed. These residences, which are called "Housh" with traces of the Ottoman and Qaramanli Periods, are buildings shaped around a courtyard. In fact, these "Housh", which combine the characteristics of the Mediterranean architecture plan with local materials and techniques, have suffered from long-term disuse. Today, lack of financial resources, combined with a lack of historical consciousness, created a different demographic and social structure in the historical city. The primary aim of the thesis is to document the current situation, to examine the sustainability of "Housh" type structures and to develop suggestions for sustainability of the Libyan Housh. based on research on websites, articles, and books, which deals with the idea of knowledge of environmental assessment and personal impressions of the place is good knowledge and we can provide the reader with new information on this subject.